Leishmania DNA detection and species characterization within phlebotomines (Diptera: Psychodidae) from a peridomicile-forest gradient in an Amazonian/Guianan bordering area - Vasconcelos dos Santos, Thiago (PLoS One, 2019)
In the border region between Brazil and French Guiana, American cutaneous leishmaniasis is a worrisome public health issue, and entomological studies are required there to better identify classical and putative emerging transmission patterns. The present study aimed to detect and characterize Leishmania DNA in the phlebotomine population of Oiapoque (Amapá State, Brazil). Phlebotomines were captured in anthropized and wild environments in the outskirts of Oiapoque municipality, using CDC light traps installed in vertical (ground/canopy level) and horizontal (peridomicile/extradomicile/forest-edge/forest) strata. Captured specimens were identified according to their morphology. Females were processed for Leishmania DNA detection and characterization using a multiplex polymerase chain reaction targeting kinetoplast DNA (kDNA) and the phlebotomine cacophony gene. The kDNA positive samples were characterized by cloning and sequencing the Leishmania 234 bp-hsp70 gene. Among the 3957 phlebotomine specimens captured, 26 pooled female samples were positive for Leishmania (Viannia) spp. DNA. Sequencing analysis allowed species-specific identification of L. (V.) braziliensis DNA in Trichophoromyia ininii, Bichromomyia flaviscutellata, Nyssomyia umbratilis, and Evandromyia infraspinosa, and L. (V.) guyanensis DNA in Ny. umbratilis. A pooled sample of Ny. umbratilis was positive for both L. (V.) braziliensis and L. (V.) guyanensis DNA. The present study provided additional information regarding ACL ecology in Oiapoque, highlighting the presence of L. (V.) braziliensis DNA in different phlebotomine species. The epidemiological implications of these findings and the determinant incrimination of L. (V.) braziliensis as proven vectors in that region must be clarified. In this regard, studies on Leishmania spp. infection and suggestive anthropophilic behavior of associated phlebotomines need to be prioritized in entomological surveillance.